2014
DOI: 10.1080/07448481.2014.963106
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Health and Adjustment to College Life for Student Service Members/Veterans

Abstract: Implications for improved behavioral health screening and coordination of university behavioral health services with veterans' health systems are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…PTSD symptoms of student veterans significantly correlate with low levels of academic adjustment (Ingala, Softas-Nall, & Peters, 2013;Schonfeld et al, 2015) and lower self-efficacy for learning (Ness, Middleton, & Hlidebrandt, 2015;Ness & Vroman, 2014). Student veterans with more severe symptoms of depression also reported significant difficulties in adjusting to university life (Schonfeld et al, 2015). They also have significantly poorer academic performance and lower graduation rates (Herrmann, Hopkins, Wilson, & Allen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…PTSD symptoms of student veterans significantly correlate with low levels of academic adjustment (Ingala, Softas-Nall, & Peters, 2013;Schonfeld et al, 2015) and lower self-efficacy for learning (Ness, Middleton, & Hlidebrandt, 2015;Ness & Vroman, 2014). Student veterans with more severe symptoms of depression also reported significant difficulties in adjusting to university life (Schonfeld et al, 2015). They also have significantly poorer academic performance and lower graduation rates (Herrmann, Hopkins, Wilson, & Allen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Simply watching or reading the news can inform educators that many veterans, especially those who deployed in recent conflicts and are currently in the civilian sector looking for work and/or attending college, are at risk for a variety of health issues including alcohol and drug abuse, homelessness, and suicide. 39 Nursing faculty are in a position to use education as a means to improve their social status, and ultimately their health and well-being. Not to mention, modeling for these students a way for them to succeed and find a sense of purpose in a profession they are seeking a career.…”
Section: Data Support Cultural Sensitivity and Development Of Humilitmentioning
confidence: 99%
“…Further, the increasing need for advisors and counselors to gain additional training to work with students who are experiencing PTSD, service-related disabilities, or other life-altering circumstances is suggested (Borsari et al, 2017;Cole, 2013;Spencer, 2016). For example, Schonfeld et al (2015), found that almost 30% of SSM/V identified difficulties in adjusting to college, and were more likely to report a history of mental health concerns during and after their military experiences. Providing support for SSM/V organizations as important resources to promote social connections for SSM/V on college campuses is also recommended (Summerlot, Green, & Parker, 2009).…”
Section: Implications For Student Affairs Professionals University Pementioning
confidence: 99%